2012
DOI: 10.2135/cropsci2011.05.0267
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Quantitative Trait Loci Analysis of Drought Tolerance in a Spring Wheat Population Using Amplified Fragment Length Polymorphism and Diversity Array Technology Markers

Abstract: Water availability is commonly the most limiting factor for crop production. This study was conducted to map wheat {Triticum aestivum L.) quantitative trait loci (QTL) involved in drought tolerance. Using amplified fragment length polymorphisms (AFLPs) and Diversity Array Technology (DArT) markers, a population of 122 F-,-derived recombinant inbred lines from a cross between 'Dharwar Dry' and 'Sitta' was reanalyzed to identify previously unknown QTL associated with drought tolerance traits and to further satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
3
18
0
3
Order By: Relevance
“…Two genomic regions were identified on chromosome 4A associated with yield stability coefficient ( Table 2 ), of which the first within a 4.8 cM interval explaining 12% of the variation (identified by markers M6564, M612 and M8365) represents a novel genomic region with almost similar effects on GY in the different environments. The second genomic region on chromosome 4A at 233.7 cM, with higher allelic effects in irrigated environment compared to stress environments, is within 1.8 to 7.4 cM from QTL reported to be associated with GY, DSI and HI on chromosome 4AL 13 17 35 36 . The genomic region identified at 153.6 cM on chromosome 5B most likely falls in the region of the stable QTL for GY identified in three elite populations under irrigated environments by GWAM 15 .…”
Section: Resultsmentioning
confidence: 87%
“…Two genomic regions were identified on chromosome 4A associated with yield stability coefficient ( Table 2 ), of which the first within a 4.8 cM interval explaining 12% of the variation (identified by markers M6564, M612 and M8365) represents a novel genomic region with almost similar effects on GY in the different environments. The second genomic region on chromosome 4A at 233.7 cM, with higher allelic effects in irrigated environment compared to stress environments, is within 1.8 to 7.4 cM from QTL reported to be associated with GY, DSI and HI on chromosome 4AL 13 17 35 36 . The genomic region identified at 153.6 cM on chromosome 5B most likely falls in the region of the stable QTL for GY identified in three elite populations under irrigated environments by GWAM 15 .…”
Section: Resultsmentioning
confidence: 87%
“…High reproducibility, rapid generation and high frequency of identifiable polymorphisms make AFLP analysis an attractive technique for determining linkages by analyzing individuals from segregating populations (Alexander et al, 2012). AFLPs are more reproducible than RAPDs (Savelkoul et al, 1999), thus are more reliable for population and genetic studies.…”
Section: Amplified Fragment Length Polymorphismmentioning
confidence: 99%
“…For example, Merchuk-Ovnat et al (2016) showed that the introgression of QTLs on chromosomes 1B and 2B of T. turgidum into T. aestivum can enhance drought tolerance in domesticated wheat. On the other hand, a number of studies have proposed that chromosome 4A has an important role to play in drought tolerance (Alexander et al, 2012;Edae et al, 2014;Kumar et al, 2012;Nezhad et al, 2012). For instance, Edae et al (2014) found chromosome regions (on 4A) that were associated with drought tolerance related traits such as the drought susceptibility index, leaf senescence, green leaf area and flag leaf traits.…”
Section: Introductionmentioning
confidence: 99%